PERTANGGUNGJAWABAN PIDANA TERHADAP KONTRAKTOR DALAM HAL TERJADI KECELAKAAN KERJA MENURUT UNDANG – UNDANG NOMOR 3 TAHUN 1992 TENTANG JAMINAN SOSIAL TENAGA KERJA - Hana Pritanti, Purwoto, Solechan (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Work accidents are accidents that occurred in connection with the employment relationship, including diseases arising from the employment relationship, as well as accidents that occur on the way from home to go to work, and come home with the usual or normal path traversed. Workplace accidents is also a risk that must be faced by the workers / laborers. In this case the workers covered by the Act - Act No. 13 of 2003 on Employment and Law - Law No. 3 of 1992 on Social Security Workers. Given the accident should be accounted for, of course, in this case related to criminal responsibility. Based on the survey results revealed many factors that caused the accident, that human error factors, equipment factors, and environmental factors. In case of accidents, the contractor is the party that is responsible. Accountability may be the form of fees or compensation to the workers involved in the accident. However, many contractors that do not provide cash compensation contributions or workers. This resulted in the contractor may be liable in accordance with Law No. 3 of 1992 on Social Security Workers. Therefore, it is necessary oversight of the workings of a construction services company, as well as the dissemination of the importance of social security to the public and employers.